Proposta de um novo algoritmo de roteamento para redes de sensores sem fio e estudo de uma técnica para prover QOS nestas redes - Eduardo Habib Bechelane Maia (2006)
This work presents two main contributions. First, it shows the Inter Cluster Routing Algorithm (ICA), a new and efficient routing algorithm for wireless sensor networks based on the Low-Energy Adaptive Clustering Hierarchy (LEACH) [1] algorithm. The proposed algorithm, when compared with LEACH and LEACH-C [2], presents not only higher network lifetime but also a higher number of delivered messages. The energy maps also show that ICA presents a better energy distribution and degradation, when compared to LEACH and LEACH-C [2]. ICA is indicated to sensor networks that collect data periodically and in which the network lifetime is an important parameter. The second contribution of this work is the Overlay for WireLess sensor networks (OWL) algorithm. We show that the se of overlay networks on Wireless Sensor Networks (WSN) can increase the Quality of Service (QoS) of such networks at a low cost. In our experiments we observe that the use of overlay networks over WSNs can decrease the packet loss of priority packets, in 68.5% being only 14.36% higher than the best possible result. Experiments with heterogeneous traffic in terms of QoS requests showthat OWL can handle such traffic and treat each packet in accordance to it QoS requests. In this way we can have a cheap way to increase the QoS over Wireless Sensor Networks using, basically, the already existent protocols and structure, even for networks with packets with different QoS requests.